An intervention study on occupational safety and health management at a vocational college in Perak - Nur Hidayah, Harith (2019)
This is an intervention study on occupational safety and health management at a vocational school in Perak. Statistics show that accident rates in Europe are high among young workers. Thus, this study was carry out in hope to lessen the rate of incident among young workers or soon-to-be young workers. The first objectives of this study were to determine the level of occupational safety and health (OSH) management implementation in school. Second, to measure level of knowledge and awareness the students have on occupational safety and health (OSH) management in school and third, to measure the effectiveness of the intervention of occupational, safety and health (OSH) management that had been done on the students. The research design for this study is interventional study design where pre-post study design was used. The study population was the students of the vocational college. The research instrument used were recording devices, observation checklist, questionnaires and Statistical Package for the Social Sciences (SPSS) Software. For result, all objectives were achieved. The level of implementation of the occupational safety and health management at the vocational college was above average. The level of implementation of occupational safety and health (OSH) management in the vocational college reached level 4 or close to completion. Meanwhile for level of knowledge and awareness of the students were also above average. The knowledge and awareness level of the vocational students were high according to the interpretation level referred to in the study. The intervention done to the students was effective based on the result because more than half of the questions in the questionnaires showed difference between pre-intervention and post-intervention. To conclude, the level of implementation of occupational safety and health (OSH) management in the vocational college is close to completion. Meanwhile, the knowledge and awareness of the students on occupational safety and health (OSH) management high with average mean of 3.5 above. Lastly, the intervention done on occupational safety and health (OSH) management to the students was effective. Recommendation for this study were safety education improvement in school and the effectiveness of occupational safety and health education and training.